The IGF2/IGF1R/Nanog Signaling Pathway Regulates the Proliferation of Acute Myeloid Leukemia Stem Cells - Xu, Dan-dan; Wang, Ying; Zhou, Peng-jun; Qin, Shu-rong; Zhang, Rong; Zhang, Yi; Xue, Xue; Wang, Jianping; Wang, Xia; Chen, Hong-ce; Wang, Xiao; Pan, Yu-wei; et al. (Frontiers in Pharmacology, 2018)
Acute myeloid leukemia (AML) is an aggressive disease characterized by clonal proliferation of dysfunctional myeloid precursors and their differentiation into immature hematopoietic cells. Accumulating evidence shows that leukemia stem cells CD34+CD38- (LSCs) are responsible for drug resistance, metastasis, and relapse of leukemia. In this study, we found that Nanog is significantly overexpressed in LSCs populations from acute myeloid leukemia (AML) patients and leukemia cell lines. Our data demonstrated that knockdown of Nanog inhibited proliferation, induced cell cycle arrest and cell apoptosis. Moreover, Nanog silence suppressed the leukemogenesis of LSCs in mice. In addition, it was found that these function of Nanog was regulated by IGF1R signaling pathway. Nanog overexpression can rescue the colony formation ability in Picropodophyllin (PPP)-treated LSCs. In contrast, knockdown of Nanog abolished the effects of IGF2 on colony formation ability of these LSCs. These findings suggeset that IGF2/IGF1R/Nanog pathway plays a critical role in LSCs proliferation and leukemogenesis.